PERSOALAN MAGIS DALAM KABA PUTI NILAM CAYO KARYA SJAMSUDIN SUTAN RAJO ENDAH - Suria Dewi Fatma (Universitas Andalas, 2010)
This article describes magical contents in kaba Puti Nilam Cayo. Intrinsic aspects were analized with structural approach. After that, the results were analized with sociological approach. After all, this object describes magical contents as rutinity and as symbols. This kaba shows Minangkabaunesse believe in supernatural activity in their universe.